PENGEMBANGAN GAME EDUCATION BERBASIS ANDROID TERHADAP KEMAMPUAN COMPUTATIONAL THINKING DALAM MATERI TIK PADA SISWA KELAS VIII SMPN 2 PONTIANAK - Agun Saputro, Alexander; Darma, Yudi; Puspitasari, Henny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was carried out with the aim of producing an Android-based educational game for Computational Thinking abilities in ICT material for class VIII students at SMPN 2 Pontianak. This research uses the Research and Development (R&D) research method by applying the ADDIE research model which is in accordance with the Research and Development research stages. In this research there are two research subjects, namely product development subjects and product trial subjects. Data collection techniques in this development research are interviews, documentation and indirect communication. Meanwhile, the data collection tools used were interview guides, documentation, and validation sheets in the form of respondent questionnaires and expert validation. The findings from research on the development of Android-based educational games on computational thinking abilities in ICT materials in class VIII students at SMPN 2 Pontianak are a learning medium in the form of an Android digital (technology-based) game with the name EDUTIK game which is used as a learning medium in schools. The results of this research produced educational games with a validity level of 91.4% (Very Valid), Practical 94.3% (Very Practical), and an effectiveness level of 90.2% (Very Effective). In the sense that the educational game that has been developed can be said to be suitable for use as a digital learning medium and can improve the computational thinking abilities of class VIII students at SMPN 2 Pontianak.